2007
DOI: 10.1126/science.1136256
|View full text |Cite
|
Sign up to set email alerts
|

Eddy/Wind Interactions Stimulate Extraordinary Mid-Ocean Plankton Blooms

Abstract: Eddy-wind interactions stimulate extraordinary mid-ocean plankton bloomsOne-sentence summary: Mid-ocean eddies, together with wind-forced motions, cause episodic bursts of nutrient supply to the upper ocean, changes in plankton community structure, and export of organic material to the deep sea. Understanding the controls on primary production in the upper ocean is of fundamental importance for two main reasons. First, primary productivity sets a firstorder constraint on the energy available to sustain oceani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
693
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 755 publications
(773 citation statements)
references
References 35 publications
(2 reference statements)
33
693
2
10
Order By: Relevance
“…This variability likely reflects both enduring climatological differences within regions and transient, localized processes, such as storms, mesoscale eddies, horizontal advection of distinct water masses, tidal mixing and bathymetry (Greene et al, 2012;Mahadevan et al, 2012;McGillicuddy et al, 2007). Finally, our analysis compares well to the seasonal averages described for the Gulf of Maine by Thomas et al (2003) and differ from the descriptions of bloom initiation in Ji et al (2007) and Song et al (2010) because their study domains extended further north and eastward over the shallower areas of the Scotian Shelf.…”
Section: Discussionsupporting
confidence: 56%
“…This variability likely reflects both enduring climatological differences within regions and transient, localized processes, such as storms, mesoscale eddies, horizontal advection of distinct water masses, tidal mixing and bathymetry (Greene et al, 2012;Mahadevan et al, 2012;McGillicuddy et al, 2007). Finally, our analysis compares well to the seasonal averages described for the Gulf of Maine by Thomas et al (2003) and differ from the descriptions of bloom initiation in Ji et al (2007) and Song et al (2010) because their study domains extended further north and eastward over the shallower areas of the Scotian Shelf.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, overall production may be enhanced by higher light levels or nutrient availability, or the absence of grazers. Besides wintertime mixing, recent studies have shown the importance of mesoscale eddies to nutrient supply in the subtropical gyre (McGillicuddy et al, 1998;Siegel et al, 1999;McGillicuddy et al, 2007). However, the same eddy effects were shown to have an opposite effect in the Labrador Sea (McGillicuddy et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
“…A strong eddy (e.g., ring) tends to trap water masses in its interior region, but this is not the case for a weak eddy (McWilliams and Flierl 1979;Chelton et al 2011) and for a meander of a jet (Cushman-Roisin 1993). A propagation tendency and the corresponding upwelling structure are also different between a ring and a meander (Cushman-Roisin et al 1990, 1993Mariano et al 1996;Martin and Richards 2001;McGillicuddy et al 2007). Important questions remain unanswered:…”
Section: Introductionmentioning
confidence: 97%
“…Also, a ring acts to remove energy from the jet and reduce a potential vorticity gradient associated with the jet (Olson 1991;Bush et al 1995), while may reinforce the jet by momentum flux convergence (e.g., Waterman and Hoskins 2013). In addition, a ring is often accompanied by strong upwelling structure (e.g., Martin and Richards 2001;McGillicuddy et al 2007), which is important in marine ecosystems by vertically transporting nutrients into the euphotic zone. In the KE region, the rings shed from the jet and their importance have been reported (e.g., Mizuno and White 1983;Kawamura et al 1986;Oka et al 2011).…”
Section: Introductionmentioning
confidence: 99%